2013
DOI: 10.1111/jth.12130
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of Canadian type 3 von Willebrand disease: further evidence for co-dominant inheritance of mutant alleles

Abstract: Summary Background Type 3 von Willebrand disease (VWD) is the most severe form of the disease and is classically inherited in an autosomal recessive fashion. Objectives The aim of the current study was to investigate the molecular pathogenesis of a Canadian cohort of type 3 VWD patients. Patients/Methods 34 families comprised of 100 individuals were investigated. Phenotypic data, including bleeding scores (BS), von Willebrand factor (VWF) laboratory values, and anti-VWF inhibitor status were included as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
107
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(127 citation statements)
references
References 39 publications
20
107
0
Order By: Relevance
“…With regard to type 3 VWD, some have used this category to include those with minimal residual VWF levels (ie, <5 IU/dL) 6. Others consider any detectable VWF to represent type 1 VWD, albeit a more severe phenotype, and reserve the label of type 3 VWD for those with completely undetectable VWF levels 2, 7.…”
Section: Classification Of Von Willebrand Diseasementioning
confidence: 99%
“…With regard to type 3 VWD, some have used this category to include those with minimal residual VWF levels (ie, <5 IU/dL) 6. Others consider any detectable VWF to represent type 1 VWD, albeit a more severe phenotype, and reserve the label of type 3 VWD for those with completely undetectable VWF levels 2, 7.…”
Section: Classification Of Von Willebrand Diseasementioning
confidence: 99%
“…20 The disease is transmitted as either a recessive trait (normal parents) or through the inheritance of 2 mutant codominant alleles (both parents have type 1 VWD). 21 The .110 type 3 VWD cases that have been genetically characterized show a range of VWF mutations, from large VWF deletions through a miscellany of null mutations to missense mutations that prevent VWF biosynthesis and secretion. Although initial studies of the infrequent cases of type 3 VWD developing alloantibodies to VWF showed an association with VWF deletion mutations, 22,23 there has been no systematic confirmation of this observation.…”
Section: Type 3 Vwdmentioning
confidence: 99%
“…The severity of these patients' bleeding symptoms was evaluated using the Condensed MCMDM-1VWD BAT where a BS of $4 denotes abnormal bleeding. 9 Peripheral blood samples were taken to obtain plasma, genomic DNA, and BOECs from these patients. Putative splicing mutations were confirmed though Sanger DNA sequencing (supplemental Table 1, available on the Blood Web site).…”
Section: Patients: Genotyping and Phenotypingmentioning
confidence: 99%
“…by guest www.bloodjournal.org From VWF:Ag and VWF:RCo levels lower than 0.5 IU/mL, and abnormal BS $4 using the MCMDM-1VWD BAT (Table 1). 9 The first family (with patients V69 and V70) exhibited significant mucocutaneous bleeding with positive BSs and correspondingly low VWF and FVIII plasma levels ( Table 1). Both patients were heterozygous for the exonic mutation c.3538G.A in exon 26 of VWF.…”
Section: Patient Genotypes and Phenotypesmentioning
confidence: 99%